Atmospheric deposition of antimony in a typical mercury-antimony mining area, Shaanxi Province, Southwest China. (February 2019) - Ao, Ming; Qiu, Guangle; Zhang, Chao; Xu, Xiaohang; Zhao, Lei; Feng, Xinbin; Qin, Song; Meng, Bo
Abstract: Mercury-antimony (HgSb) mining activities are important anthropogenic sources of Hg and Sb to the local environment. The Xunyang HgSb mine situated in Shaanxi Province is an active Hg mine in China. To understand the emission, transportation, and deposition of Sb through HgSb mining activities, current study systematically monitored the Sb concentration in precipitation in the Xunyang HgSb mining district. Five groups of experimental pots were carefully designed to further investigate the influence of HgSb mining activities on the Sb contamination in the local surface soil. Based on the overtime increasing of the Sb concentrations in soil from experimental pots, for the first trial, we estimated the atmospheric deposition flux/mass of Sb in the Xunyang HgSb mining district. Our results showed that the concentrations of Sb in precipitation in the Xunyang HgSb mining district ranged from 0.71 μg L −1 to 19 μg L −1 (mean = 4.2 ± 4.5 μg L −1 ), which was orders of magnitude higher than that at the control site. As expected, the concentration of Sb in precipitation was highly elevated near of the HgSb smelter and gradually decreased with distance from the smelter. After 12 months exposure, Sb concentrations in soil of experimental pots were increased by 1.2–8.5 times. The average atmospheric wet and dry deposition flux of Sb in the Xunyang HgSb mining district were 7.2 ± 6.9 μg m −2 day −1 and 2.1 ± 4.7 mg m −2 day −1, respectively; the annual wet and dry deposition mass of Sb through HgSb mining activities were estimated to be 1.6 t y −1 and 158 t y −1, respectively, indicating that dry deposition was the dominant pathway (98 ± 1.2%) for the removal of Sb from the atmosphere. Our results confirmed that the ongoing HgSb mining activities resulted to serious Sb contamination to terrestrial ecosystems, posing a potential threat to local residents in the Xunyang HgSb mining district. Graphical abstract: Highlights: Sb concentrations in precipitation and rice paddy soil were highly elevated near of the HgSb smelter. Dry deposition was the dominant pathway for the removal of Sb from the atmosphere. The ongoing HgSb mining activities resulted to serious Sb contamination to surface terrestrial ecosystems. Abstract : Dry deposition was the dominant pathway for removal of Sb from the atmosphere and the ongoing HgSb mining activities resulted to serious Sb contamination to surface terrestrial ecosystems.